High Security Text and Image Message for Steganography and Watermarking Through Modified Least Significant Bits Technique - Ahirwar, Bhawna; Sharma, Sanjay K (International Journal of Computer Sciences and Engineering, 2025)
Steganography” is a technique that thwarts unauthorized users to have access to the crucial data, to invisibility and payload capacity using the different technique like discrete cosine transform (DCT) and discrete shearlet transform (DST).The available methods till date result in good robustness but they are not independent of file format. The aim of this research work is to develop a independent of file format and secure hiding data scheme. The independent of file format and secure hiding data scheme is increased by combining DST and least significant bits (LSB) technique. Accordingly an efficient scheme is developed here that are having better MSE and PSNR against different characters